O trabalho dos professores em contextos de gestão escolar - Liliana Soares Ferreira (Universidade do Minho, 2010)
In this article, I present arguments, systemize relations between the pertaining to school management and the work of the teachers. I consider that the management processes, in the pertaining to school contexts, are implied and, in a similar way, intervene with the work of the teachers who are the production of the lesson and the knowledge. When being carried through collective and democratic efforts of management, they go, if configuring the professional conditions and possibilities, in movements of knowledge and power, disclosed in the language, in the daily pertaining to school.